2021
DOI: 10.1111/jvh.13477
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary seroepidemiology of viral hepatitis and the gap in hepatitis C care cascades among uraemic patients receiving haemodialysis in Taiwan—the Formosa‐Like Group

Abstract: Uraemic patients undergoing haemodialysis are at high risk of hepatitis B virus (HBV) and hepatitis C virus (HCV) infection. We aimed to evaluate the evolutionary seroprevalence of viral hepatitis and the gap in HCV care cascades in this special population by a large-scale surveillance study in Taiwan. Uraemic patients on maintenance haemodialysis from 22 sites (FORMOSA-LIKE group) in 2012 (n = 1,680) and 2019 How to cite this article: Wei Y , Hsu P , Lee J , et al. Evolutionary seroepidemiology of viral hepat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
(58 reference statements)
0
4
0
Order By: Relevance
“…The mean positivity rate for HCV antibodies in outpatients with kidney disease, excluding those with ESRD, was 5.7% in our hospital and was higher than that in the general population (4.1%) in the same county (Changhua) [19]. Although we know that uremic patients with ESRD in Taiwan (Kaohsiung) have a high anti-HCV seropositivity rate (13.6%) [20], no studies have focused on HCV screening in patients with kidney disease other than ESRD. The higher HCV rate in patients with kidney disease may be associated with chronic hepatitis C infection, which can induce insulin resistance and chronic inflammatory responses that have been linked to an increased risk of DM and CKD [3].…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…The mean positivity rate for HCV antibodies in outpatients with kidney disease, excluding those with ESRD, was 5.7% in our hospital and was higher than that in the general population (4.1%) in the same county (Changhua) [19]. Although we know that uremic patients with ESRD in Taiwan (Kaohsiung) have a high anti-HCV seropositivity rate (13.6%) [20], no studies have focused on HCV screening in patients with kidney disease other than ESRD. The higher HCV rate in patients with kidney disease may be associated with chronic hepatitis C infection, which can induce insulin resistance and chronic inflammatory responses that have been linked to an increased risk of DM and CKD [3].…”
Section: Discussionmentioning
confidence: 51%
“…The HCV viremia rate was also higher in the baseline group than in the screening group (69.1% vs. 46.8%). The FORMOSA-LIKE group by Yu-Ju Wei1 et al [20] showed that the HCV viremia rate decreased after an 8-year follow up in uremic patients (73.8% to 56.3%) and that the HCV treatment rate increased from 2.3% to 21.7%. However, the treatment rate in patients without viremia was higher in the baseline group than in the screening group (11.6% vs. 5.1%) in our study, and the rate of anti-HCV signal-to-cutoff (S/CO) ratio ≥ 10.9 in patients without viremia was also higher in the baseline group than in the screening group (12.3% vs. 3.9%).…”
Section: Discussionmentioning
confidence: 99%
“…To address the considerable prevalence of HCV patients in remote rural and mountainous areas, as well as the glaring scarcity of medical resources, we have established several approaches, including the establishment of sentinel medical institutions, expansion of testing capacity, and intensification of public awareness and education efforts, 25 and in addition, for the villages and towns with high prevalence of hepatitis C, we have taken targeted measures such as centralized screening, centralized diagnosis and treatment, and supervision in rural areas. Hepatitis C clinic determines the third Wednesday of every month as ‘Hepatitis C Day’, and carries out Hepatitis C clinic and free screening activities once a month 26 . It is worth noting that while our study has made progress towards achieving the overall goal set by the World Health Organization, there are still some patients who did not complete the diagnosis and treatment process.…”
Section: Discussionmentioning
confidence: 99%
“…Hemodialysis patients are at a greater risk of chronic hepatitis C virus (HCV) infection, 1 which have been associated with multiple comorbidities 2 , co-medication and frequent drug-drug interaction with directly-acting antiviral agents. 3 We read the report with great interest in an issue of Journal of Hepatology 4 .…”
Section: To the Editormentioning
confidence: 99%